2015
DOI: 10.1021/acs.jpcc.5b05292
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Exciplex Emitters Using Donor–Acceptor Type Acceptor Material

Abstract: A design rule of the acceptor material of exciplexes was studied by synthesizing two acceptor materials with only acceptor moieties and with both a donor and an acceptor simultaneously. Molecular calculation and photophysical measurements of the exciplexes revealed that the donor−acceptor type acceptor materials promoted the exciplex formation by charge transfer character and increased the photoluminescence quantum yield of the exciplexes. The combination of a donor material and the donor−acceptor type accepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…High EQE exciplexes were also reported by mixing an n‐type acceptor with an intramolecular TADF material. The TADF material is a kind of bipolar material with a donor–acceptor structure and it could make the intermolecular type exciplex with the n‐type or p‐type material . For instance, 6‐(9,9‐dimethylacridin‐10(9H)‐yl)‐3‐methyl‐1H‐isochromen‐1‐one (MAC):PO‐T2T exciplexes were derived from a n‐type acceptor and an TADF emitter .…”
Section: External Quantum Efficiency Current Efficiency and Color Cmentioning
confidence: 99%
“…High EQE exciplexes were also reported by mixing an n‐type acceptor with an intramolecular TADF material. The TADF material is a kind of bipolar material with a donor–acceptor structure and it could make the intermolecular type exciplex with the n‐type or p‐type material . For instance, 6‐(9,9‐dimethylacridin‐10(9H)‐yl)‐3‐methyl‐1H‐isochromen‐1‐one (MAC):PO‐T2T exciplexes were derived from a n‐type acceptor and an TADF emitter .…”
Section: External Quantum Efficiency Current Efficiency and Color Cmentioning
confidence: 99%
“…To realize efficient TADF OLEDs based on exciplex, the donor and acceptor materials should: a) possess proper HOMOs and LUMOs, other than would not forming intermolecular CT; [13] b) have lowest triplet energy levels (T 1 s) not lower than the CT states ( 1 CT and 3 CT) to prevent the energy leakage from exciplex to donor or acceptor; [12,[15][16] c) have strong electron donating and electron accepting characteristics to facilitate the forming of exciplex. [22] And it was found that donor-acceptor (D-A) type molecule would possess stronger electron donating or electron accepting characteristics. [22] Besides, exciplex can not only realizing TADF emission, but also can be used as host sensitizing phosphorescent, fluorescent and TADF emitters.…”
Section: Introductionmentioning
confidence: 99%
“…[22] And it was found that donor-acceptor (D-A) type molecule would possess stronger electron donating or electron accepting characteristics. [22] Besides, exciplex can not only realizing TADF emission, but also can be used as host sensitizing phosphorescent, fluorescent and TADF emitters. And exciplex host based OLEDs normally exhibit good device performance because exciplex host has the advantages of bipolar charge transporting, wide exciton recombination zone and barrier free from hole transporting layer (HTL) and electron transporting layer (ETL) to the emitting layer (EML).…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of bimolecular TADF lags far behind. Most exciplex-type TADF OLEDs showed maximum EQE close to 10% (Jankus et al, 2014; Liu et al, 2015a,b; Oh et al, 2015; Zhang L. et al, 2015; Hung et al, 2016, 2017; Jeon et al, 2016), with only one example approaching to 18% (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%